Complete business statistics - Amir D. Aczel (McGraw-Hill, 2002)
File dalam bentuk Gambar, Excel, PDF, Htm (Internet), dll; Isi: DataSets, Help, MultiAnalysis, PPT, Quizzes, Templates, Viewers, VisualStatistic 2.0 (Excel Files, Icon, Programs,Reader, Setup, Sound, VsData, dll) , Weblinks, dll; Judul dalam kemasan.